Success of the Breeding Cattle Kadasan Program in Beririjarak Village, Wanasaba, East Lombok: A Second Evaluation After Two Years of Implementation - Mohammad Hasil Tamzil; Hailuddin (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
The breeding cattle kadasan program initiated by the Indonesian Ulema Council of West Nusa Tenggara Province (MUI-NTB) has been implemented for the past two years and needs to be evaluated to assess its progress and identify challenges encountered during its implementation. The evaluation was carried out through direct field observations at the cattle farming site, as well as interviews with farmers and local village officials. The results showed that the livestock farming activities have continued to operate well, as indicated by an increase in cattle population from 9 to 12 head. The housing facilities were found to be relatively good, more spacious, and well maintained, thereby supporting better animal health and management. Nevertheless, one case of calf mortality following parturition was reported. Overall, the cattle were in good health condition and exhibited satisfactory growth performance. In addition, farmers’ motivation and enthusiasm for cattle farming increased significantly, particularly after participating in training programs on silage production and organic fertilizer processing. Based on the evaluation findings, it can be concluded that the cattle kadasan program developed by MUI-NTB has been successfully implemented and shows strong potential to enhance both the welfare and farming capacity of local farmers.